THEATRE AS A MEDIUM OF INFOTAINMENT AND SOCIAL DEVELOPMENT - Sharma, Abhishek (ShodhKosh: Journal of Visual and Performing Arts, 2023)
We live in a country which is diverse with the presence of different caste, language, culture, custom, religion, creed and tribes. This paper is trying to explore how theatre works as a tool for the social development and how it is helpful for the developmental aspects of the society. And as a medium of infotainment, how theatre is helpful for bringing the change and highlights the issues of the society. Theatre is a useful medium for the social development and promotes growth. It is one of the most powerful medium for developmental activities and it conveys messages for both Socioeconomic development of the society. Several themes such as education, agriculture, sanitation and hygiene, water conservation, child labor, child marriage, human rights, corruption, caste discrimination, women empowerment, awareness of disease, family planning, vaccination, nutrition, environment pollution, communal harmony etc. This proposed paper is an attempt to ensure the use of theatre to reach the common people by interacting and involving them in the process of change and development of the country.